2018
DOI: 10.1108/ils-11-2017-0114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender on attitude towards the use of social media for continuing professional development among academic librarians in Nigeria

Abstract: Purpose The purpose of this paper is to investigate the influence of gender on attitude towards the use of social media for continuing professional development among academic librarians in Ogun State, Nigeria. Design/methodology/approach Descriptive survey design was used for the study. Research instrument used was questionnaire where 79 copies were administered to academic librarians, using total enumeration sampling technique. Five universities in Ogun State, Nigeria were selected for the study. The data c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…School's role in supporting teachers' SM use could help strengthen teachers' online collaboration more specific and relevant to their own capacity needs. The analysis is in line with what Anasi (2018) suggests that SM has the potential for teachers' professional growth and development. In particular, teachers in developing countries like Pakistan with minimal ICT integration capacity, found by Ismail et al (2020), could be supported to overcome their fear and digital anxiety (Beemt et al, 2019;Kormos and Nijakowsk, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…School's role in supporting teachers' SM use could help strengthen teachers' online collaboration more specific and relevant to their own capacity needs. The analysis is in line with what Anasi (2018) suggests that SM has the potential for teachers' professional growth and development. In particular, teachers in developing countries like Pakistan with minimal ICT integration capacity, found by Ismail et al (2020), could be supported to overcome their fear and digital anxiety (Beemt et al, 2019;Kormos and Nijakowsk, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…The theory encompasses the links between behavioral intention, behavioral attitudes, and subjective norms. The theory has been widely used as a useful predictor of one's attitudes about networking use and SM's information sharing capability (Peslak et al, 2011;Anasi, 2018;Lin et al, 2013). Research has found the TRA relevant when the study intends to know about one's attitudes towards their behaviour.…”
Section: Theory Of Reasoned Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, learning collaboration was facilitated through Spreadsheets, Google Jam Board, and Google Docs. Social media platforms, such as WhatsApp, Messenger, Telegram, Instagram, and YouTube, were used to engage students during learning (Anasi, 2018;Jogezai et al, 2021;Van Den Beemt, Thurlings, & Willems, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These benefits will likely be found regardless of a participant’s job position or title. Therefore, administrators and supervisors in higher education may consider providing support for allowing and encouraging the use of social media, like Reddit, as a learning tool (Anasi, 2018 ).…”
Section: Discussionmentioning
confidence: 99%